2020
DOI: 10.1002/zoo.21568
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental impacts on sleep in captive Asian elephants (Elephas maximus)

Abstract: Modern zoos strive to improve standards of animal management, husbandry and welfare of their animals as part of a continual evaluation process. Elephants (Elephantidae) have received particular attention in recent years due to the challenge of providing environments which promote natural behavior and opportunities for social interaction. A number of measures have been proposed to measure wellbeing, with sleep quality increasingly being used. Sleep is a vital aspect of life for cell replenishment as well as opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Parker et al 2020 ). While data on nocturnal activity of elephants is limited, and largely focused on fully captive systems, there is some evidence that elephants may be stationary for large periods of the night (Wilson et al 2006 ; Lukacs et al 2016 ), and that activity depends on age and access to outside areas (Evison et al 2020 ) suggesting that most social activity takes place during diurnal hours. The measures of elephant sociality used in our study might have been too broad to capture any potential weak infection–sociality associations present in our study population or actually not capture specific social–infection mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al 2020 ). While data on nocturnal activity of elephants is limited, and largely focused on fully captive systems, there is some evidence that elephants may be stationary for large periods of the night (Wilson et al 2006 ; Lukacs et al 2016 ), and that activity depends on age and access to outside areas (Evison et al 2020 ) suggesting that most social activity takes place during diurnal hours. The measures of elephant sociality used in our study might have been too broad to capture any potential weak infection–sociality associations present in our study population or actually not capture specific social–infection mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it might indicate an absence of sleep-preventing stressors under zoo conditions. According to what we know about lying rest in elephants, one would expect younger individuals to have longer total lying durations per night compared to adult elephants (Evison et al, 2020;Schiffmann, Hoby et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although our knowledge of lying rest duration and influencing factors in zoo elephants has significantly increased over the past years (Evison et al, 2020 ; Finch et al, 2021 ; Holdgate et al, 2016 ; Schiffmann et al, 2020 ; Schiffmann, Hoby et al, 2018 ; Schiffmann, Knibbs et al, 2018 ; Walsh, 2017 ; Williams et al, 2015 ), some specific characteristics, including details or resting and sleeping behavior, have not been thoroughly investigated to date. The effect of changing enclosure substrate from concrete to sand was investigated in a single family group of African elephants only so far; in the adult females, the total lying duration per night and the lying bout length increased after the change in substrate (Schiffmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst no studies have defined optimal levels of rest for elephants, its importance has been increasingly recognised in recent years [ 46 , 47 , 48 , 49 , 50 , 51 ]. Elephants must lie down to engage in delta wave and rapid eye movement (REM) sleep, phases known for their restorative properties [ 52 ], and importance for optimal cognitive function [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of wild elephants indicate that they do not always engage in lying rest daily, and instead may only engage in recumbent rest every three to four nights [ 56 ]. Researchers have suggested that recumbent rest will only occur in captive elephants if they are comfortable and feel safe in their environment [ 48 , 51 , 57 ], with both the physical (e.g., soft, malleable surfaces or sand mounds) and social environment (e.g., access to compatible conspecifics) impacting on recumbence behaviour [ 46 , 50 , 51 ]. Floor space has also been identified as a potential factor which impacts on resting behaviour in captive elephants.…”
Section: Discussionmentioning
confidence: 99%